Exploring the Possible: A Unifying Cognitive and Evolutionary Approach to Art - Steen, Francis F.; Chakraborty, Santanu (Frontiers in Psychology, 2022)
Here we examine the distal causes of art in terms of an irreducibly risky search in a vast phase space of cognition and behavior. To explore means to engage in an activity that may result in a zero or negative payoff. Moreover, you may be unable to assess the risks with any certainty; the costs might spiral out of control. At the same time, the known alternatives may simply not be viable; natural selection has no problems acting on the failure to locate new habitable subspaces. This represents the hard problem of evolution: there is no recurring procedure that will reliably deliver the benefits of a successful exploration. We propose to locate the emergence of play and art in the tension between the irreducible risks of exploration and its potential benefits. We examine the complex suite of adaptations that have emerged to solve, however imperfectly, the hard problem of evolution. This includes adaptations lowering the risk of exploration, supporting behavioral and cognitive simulations, and strategies for open-ended yet loosely targeted searches. We argue that the ability to become aware of possible actions, to evaluate their respective merits, and to explore and develop new strategies of perception, thinking, and action have had a major impact on human survival and reproduction and have been subject to persistent natural selection. The arts, we suggest, represent a distinct cognitive mode of pushing the boundaries of what is familiar and known into new areas of perceptual, emotional, and agentive exploration and discovery, characterized by a proximal motivation of intrinsic enjoyment.